Unleashing Indonesia's Traditional Knowledge: Navigating Legal Challenges in a Changing Landscape - Disemadi, Hari Sutra; Sudirman, Lu (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
As a country blessed with abundant cultural elements, Indonesia holds the potential to harness traditional knowledge for the betterment of its people's lives. Unfortunately, this concept is often forgotten within Indonesian society and faces various challenges that jeopardize cultural heritage. Hence, the objective of this study is to analyze the significance of traditional knowledge and the legal hurdles that arise in regulating this concept within Indonesia's intellectual property rights framework. The findings of this normative legal research demonstrate that traditional knowledge holds great importance for Indonesian society, particularly amidst the accelerating impacts of globalization, which pose a threat to cultural heritage. Taking a legislative approach, there is an urgent need for a normative framework to protect traditional knowledge as a communal intellectual asset in order to realize the implicit recognition reflected in the constitution, the 1945 Constitution.